A case study of sewage sludge treatment - Hidayatur Afifah Binti Anuar (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This project is about treating the sewage sludge also known as wastewater in order to maintain a healthy environment. This study is to know how sewage sludge can be disposed safely without being danger to public health and without polluting watercourses by calculating the biochemical oxygen demand (BOD) value of watewater. In order to carry out this project, a small researched have been conducted to analyse and assessment the value of BOD in wastewater. The higher the number of BOD the more polluted the water.